(untitled) (International journal of medical sciences, 2026)
It is known that synthetic drugs do not always give the expected result. Along with the therapeutic effect, they also have side effects that make it difficult for other systems of the body to work smoothly. Medicinal plant-based drugs have almost no side effects compared to synthetic drugs. Due to the fact that various biologically active substances present in the composition increase their interaction, it has a complex effect in the treatment of various diseases.